Susceptibility of kuruma shrimp to the infection with Decapod iridescent virus 1 - Qiu, Liang; Guo, Xiao-Meng; Feng, Yong-Hui; Xing, Jing-Yi; Ren, Xian-Yun; Huang, Jie (Frontiers in Marine Science, 2023)
Infection with Decapod iridescent virus 1 (iDIV1), an important emerging disease of shrimps and crabs, has been included in the Quarterly Aquatic Animal Disease Report (QAAD) by the Network of Aquaculture Centres in Asia-Pacific (NACA) and listed by the World Organization for Animal Health (WOAH). China has classified iDIV1 as a Class II animal pandemic disease. In the present study, to determine the susceptibility of Penaeus japonicus to Decapod iridescent virus 1 (DIV1), healthy kuruma shrimp were artificially infected with DIV1 (isolate SHIV 20141215) by per os (the pathway that mimics natural transmission) and intramuscular injection (invasive pathway). The infected P. japonicus showed clinical signs such as anorexia, retardation, evident reddish body, swollen and whitish lymphoid organs, and mortalities of almost 100%. Real-time PCR showed that all the challenged individuals by per os or intramuscular routes were DIV1-positive with an average virus load between 10(9.09 ± 0.58) and 10(8.94 ± 0.45) copies/μg-DNA, respectively. Histological examination revealed karyopyknosis, and eosinophilic inclusions and minute basophilic stains were combined in lymphoid organs, hematopoietic tissue and gills of diseased individuals. In addition, lymphoid organs showed disorganization of the tubule matrix. In situ DIG-labeling loop-mediated isothermal amplification (ISDL) also demonstrated the presence of DIV1 signals existed in lymphoid organs, hemopoietic tissue, gills, epithelial tissue, hepatopancreas and muscle. Ultrathin sections examined using transmission electron microscopy (TEM) revealed the presence of DIV1 virions, the virogenic stroma, and the nucleocapsid production process in infected cells. In addition, pathogen surveillance of cultured samples showed that the DIV1 detection rate of farmed P. japonicus samples from five coastal provinces in China was 5.3% (9/157) in 2022. The results mentioned above support that P. japonicus is a newly confirmed susceptible host for DIV1, enhancing the pathogen ecological understanding of pathogens and giving more support for developing DIV1 preventive and control strategies.